First independent evaluation of QuantiFERON-TB Plus performance. Issue 5 (12th February 2016) - Barcellini, Lucia; Borroni, Emanuele; Brown, James; Brunetti, Enrico; Codecasa, Luigi; Cugnata, Federica; Dal Monte, Paola; Di Serio, Clelia; Goletti, Delia; Lombardi, Giulia; Lipman, Marc; Rancoita, Paola M.V.; et al.
Tuberculosis elimination requires an effective strategy to diagnose and treat people infected with Mycobacterium tuberculosis who would otherwise be at high risk of developing and transmitting active disease [1, 2]. The diagnostic tools for latent tuberculosis infection (LTBI) are the tuberculin skin test (TST) and the T-cell interferon-γ release assays (IGRAs). Two IGRAs are commercially available, QuantiFERON-TB Gold In-Tube (QFT-GIT) (Qiagen, Hilden, Germany) and T-SPOT.TB (Oxford Immunotec, Abingdon, UK). Compared to the TST, IGRAs offer operational advantages and higher specificity in the bacille Calmette–Guérin (BCG)-vaccinated population [3], and they are at least as sensitive for LTBI [4]. However, IGRAs have limitations: reduced sensitivity in children and immunocompromised subjects, including HIV-infected individuals [3, 4]; failure to discriminate between active tuberculosis and LTBI; and poor correlation with the risk of progression to active disease [3]. QuantiFERON-TB Plus improves sensitivity for active TB and maintains high specificity among unvaccinated controls http://ow.ly/XjYPK